Gemeinsame Managementkommission von VDB und dbv - Brandtner, Andreas; Bartlakowski, Katja; Bilo, Albert; Poth, Daniela; Untiedt, Frauke; Vonhof, Cornelia (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2017)
Abstract